Factors Associated with High Patient Activation Level among Individuals with Metabolic Syndrome at a Primary Care Teaching Clinic - Nur Hidayah Bahrom; Anis Safura Ramli; Mohamad Rodi Isa; Hasidah Abdul-Hamid; Siti Fatimah Badlishah-Sham; Noorhida Baharudin; Mohamed Syarif Mohamed-Yassin (Journal of Primary Care & Community Health, 2020)
Background: High activation level has been associated with higher education background, better self-rated health status, and having adequate health literacy. However, there is a gap in the literature regarding the level of activation and the factors associated with it among patients with metabolic syndrome (MetS) in the Malaysian primary care setting. Objectives: This study aims to determine activation levels and the factors associated with high activation among individuals with MetS in primary care. Methods: A cross-sectional study was conducted at a university primary care clinic. Patient activation was measured using the Patient Activation Measure®–13 Malay version. Activation levels were dichotomized into “low activation” (levels 1 and 2) and “high activation” (levels 3 and 4). To determine the factors associated with high activation, simple logistic regressions (SLogR) followed by multiple logistic regressions (MLogR) were performed. Results: Of 333 participants, 280 (84.1%) were included in the final analysis. The mean activation score was 59.4 (SD ±10.20) and 61.8% had high activation level. Two variables were found to be significant on MLogR. Those who were employed have the odds of 3.135 (95% CI 1.442-6.816) of having high activation compared with those who were unemployed. Those with good self-reported health status have the odds of 6.482 (95% CI 1.243-33.792) of having high activation compared to those with poor self-reported health status. Conclusions: The majority of participants had high activation levels. Those who were employed and those who had good self-reported health status were more likely to have high activation levels. Findings of this study could be used to develop patient activation interventions to improve self-management skills among individuals with MetS in primary care. These may include problem solving support, individualized care plans, peer or family support, and skill building. Those in high activation group can be trained to become mentors to support their peers who have low activation level.